The Then and There of Crip Futurity - McRuer, Robert (GLQ: A Journal of Lesbian and Gay Studies, 2014)
Review of Feminist, Queer, Crip by Alison Kafer.
Keywords: EDI; approches et analyses; capacitisme; care; corps; cours; crip; lit4700; premier cycle; ressource en ligne; systèmes d'oppressions; thématiques